THE RELATIONSHIP OF BRAND EQUITY AND PRICE WITH CUSTOMER LOYALTY OF VERMINT PRODUCTS ON CV INSAN MADANI BENGKULU - Muhamad Dwi Tanto; Ida Anggriani; Meiffa Herfianti (Penerbit Jurnal Indonesia, 2020)
Target of this research is to know relation brand equity with customer loyality of product of vermint at CV. Insan Madani Bengkulu and to know relation price with customer loyality of product of vermint at CV. Insan Madani Bengkulu. Method Analysis the used is correlation of spearman rank and hypothesis test. Pursuant to result of research obtained that correlation value of spearman rank between brand equity with customer loyality at CV. Insan Madani Bengkulu obtained by value 0,675 strong criterion because result of its correlation lay in coefficient interval between 0,600 - 0,799. From result of relation hypothesis test between brand equity with customer loyality at CV. Insan Madani Bengkulu obtained by value of t count is 6,340 so that can be concluded that brand equity (X1) have relation of significant with customer loyality at CV. Insan Madani Bengkulu because value of t count bigger than t tables (1,677). Correlation value of spearman rank between price with customer loyality at CV. Madani Bengkulu obtained by value 0,653 strong criterion because result of its correlation lay in coefficient interval between 0,600 - 0,799. From result of relation hypothesis test between price with customer loyality at CV. Insan Madani Bengkulu. obtained by value of t count is 5,972 so that can be concluded that price (X2) have relation of significant with customer loyality at CV. Insan Madani Bengkulu because value t count bigger than t tables (1,677)